The Relationship of Landslides with lithological units and fault lines occurring on the East Anatolian Fault Zone, between Palu (Elazig) and Bingol, Turkey - Avci, Vedat; Sunkar, Murat (Maden Tetkik ve Arama Genel Mudurlugu-Mta, 2018)
In this study, the relationship of landslides with lithological units and fault lines on the East Anatolian Fault Zone (EAFZ) between Palu (Elazig) and Bingol, was evaluated. In the study area, which is located within the EAFZ, Goynuk to the northeast, Palu Segment to the southwest, Genc Segment to the south of Bingol plain and Gokdere Uplift in the intersection area form the main tectonic structures. In addition, the Karakocan Fault Zone (KFZ) cutting the EAFZ in NW-SE direction between Palu and Bingol corresponds to another important structure (system). The area, which is located in a region where a number of faults intersect, is tectonically very active. This situation has affected the morphology and caused the formation of many landslides along fault lines. In order to determine the relationship between the landslides observed in this area and lithological and tectonic structures, landslide magnitude and distribution analyses were performed by means of Geographical Information Systems. For this purpose, the landslide inventory map and the database were reproduced controlling the satellite images in field studies. Similarly; geological and tectonic maps were prepared considering previous studies. Landslides created in vector format were converted into raster format and overlain with lithological and tectonic maps, and then the relationship between landslides and lithology-fault lines were determined. According to these results, 59% of landslides occur in Upper Miocene-Pliocene agglomerate and tuff units and 10% of them in Eocene carbonate units. According to these data, almost 70% of the landslides in the study area occurred in two units. Considering the relationship between landslides and fault lines 64% of the landslides are observed at 0-1000 m distances to the fault lines. As a result, there is an important relationship between lithological features and fault lines. The fact that landslides have occurred along the fault lines in the north of Murat Valley shows that the landslides are triggered more by earthquakes when compared with those triggered by the hydro meteorological events.
Keywords: System Eafs; Basin